2023
DOI: 10.1038/s41598-023-36092-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-derived exosome microRNA-21 promotes angiogenesis in multiple myeloma

Sun Miaomiao,
Wang Xiaoqian,
Shou Yuwei
et al.

Abstract: Multiple myeloma (MM) is the second most common hematological malignancy, and angiogenesis determines its progression. In the tumor microenvironment, normal fibroblasts (NFs) are transformed into cancer-associated fibroblasts (CAFs), which can promote angiogenesis. Microribonucleic acid-21 (miR-21) is highly expressed in various tumors. However, research on the relationship between tumor angiogenesis and miR-21 is rare. We analyzed the relationship between miR-21, CAFs, and angiogenesis in MM. NFs and CAFs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Of note, the exosome is promising for the cancer diagnostics ( Si et al, 2023 ). Exosomes derived from cancer cells contain specific biomarkers, such as mutant DNA, proteins, and microRNAs, that can serve as indicators of cancer presence and progression ( Ji et al, 2013 ; Miaomiao et al, 2023 ). Liquid biopsies based on exosome cargo analysis offer non-invasive methods for early cancer detection and monitoring treatment responses ( Feng et al, 2019 ).…”
Section: The Biomedical Application Of Exosomementioning
confidence: 99%
“…Of note, the exosome is promising for the cancer diagnostics ( Si et al, 2023 ). Exosomes derived from cancer cells contain specific biomarkers, such as mutant DNA, proteins, and microRNAs, that can serve as indicators of cancer presence and progression ( Ji et al, 2013 ; Miaomiao et al, 2023 ). Liquid biopsies based on exosome cargo analysis offer non-invasive methods for early cancer detection and monitoring treatment responses ( Feng et al, 2019 ).…”
Section: The Biomedical Application Of Exosomementioning
confidence: 99%
“…Researchers have found that exosomal miRNAs derived from CAFs can also participate in the process of promoting tumor angiogenesis. For example, CAF-derived exosomes promote angiogenesis by delivering miR-21 to endothelial cells in multiple myeloma ( Miaomiao et al, 2023 ). miR-135b-5p is upregulated, promoting angiogenesis in CRC cells by inhibiting thioredoxin-interacting proteins ( Yin et al, 2021 ).…”
Section: Function Of Caf-derived Exosomal Mirna In Promoting Tumorige...mentioning
confidence: 99%
“…With a full understanding of the relationship between exosomal contents and disease occurrence, exosomes are considered potential therapeutic targets and biomarkers. 161 Moreover, it stably exists in various body fluids and has the advantages of high sensitivity, low invasiveness, and easy access to materials compared with other tests, 17 which can help in the early diagnosis of diseases, detection of diseases, and evaluation of therapeutic effects (Table 1 ). 32 , 162 …”
Section: Exosome Biomarkersmentioning
confidence: 99%